ANALISIS SISTEM NON LINEAR MELALUI PENDEKATAN SISTEM LINEAR DENGAN PARAMETER BERUBAH-UBAH - widowati, widowati (MATEMATIKA, 2010)
This paper proposes the relation between nonlinear systems with LPV systems (Linear Parameter Varying systems) where the non-linear systems can be described as LPV systems. Based on the LPV systems description, the nonlinearity of the systems is represented by parameters varying. Local properties of nonlinear systems are presented. It is assumed that all the conditions for the existence and uniqueness of solutions have been met. It is also assumed that the origin is a stationary point. Then, we will discuss how to analyze the stability of non-linear systems using the LPV systems approach. Furthermore, the bounds of parameters to ensure the asymptotic stability of nonlinear systems are given. To verify the proposed method, numerical simulations are demonstrated